Respuesta :

gmany
[tex]f(x)=5x-2\\\\g(x)=2x+1\\\\(f-g)(x)=(5x-2)-(2x+1)=5x-2-2x-1=3x-3[/tex]


Answer: B. 3x - 3

Answer:

The correct option is B.

Step-by-step explanation:

The given functions are

[tex]f(x)=5x-2[/tex]

[tex]g(x)=2x+1[/tex]

We have to ind the value of (f-g)(x).

[tex](f-g)(x)=f(x)-g(x)[/tex]

[tex](f-g)(x)=5x-2-(2x+1)[/tex]

[tex](f-g)(x)=5x-2-2x-1[/tex]

Combine like terms.

[tex](f-g)(x)=(5x-2x)-2-1[/tex]

[tex](f-g)(x)=3x-3[/tex]

Therefore option B is correct.

ACCESS MORE